Genomic properties of a Bartonella quintana strain from Japanese macaque (Macaca fuscata) revealed by genome comparison with human and rhesus macaque strains - Sato, Shingo; Nishioka, Emu; Kabeya, Hidenori; Maruyama, Soichi (Scientific reports, 2024)
Bartonella quintana , the causative agent of trench fever, is an intracellular bacterium that infects human erythrocytes and vascular endothelial cells. For many years, humans were considered the only natural hosts for B. quintana ; however, it was recently discovered that wild Japanese macaques ( Macaca fuscata ) also serve as hosts for B. quintana . To elucidate the genetic characteristics of the B. quintana strain MF1-1 isolated from a Japanese macaque, we determined the complete genome sequence of the strain and compared it with those of strain Toulouse from a human and strain RM-11 from a rhesus macaque. General genomic features and orthologous gene cluster profiles are similar among the three strains, and strain MF1-1 is genetically closer to strain RM-11 than strain Toulouse based on the average nucleotide identity values; however, a significant inversion of approximately 0.68 Mb was detected in the chromosome of strain MF1-1. Moreover, the Japanese macaque strains lacked the bepA gene, which is responsible for anti-apoptotic function, and the trwL2 , trwL4 , and trwL6 genes, which may be involved in adhesion to erythrocytes of rhesus macaque and human. These features likely represent the genomic traits acquired by Japanese macaque strains in their host-associated evolution.